Orthogonal planar search (OPS) for coronary artery centerline extraction. Issue 2 (February 2016) - Tang, Szeling; Chan, Chee
Abstract In this paper, we investigate orthogonal planar search (OPS) for coronary artery centerline extraction to assist in coronary artery diseases diagnosis. The search mechanism exploits a data-driven algorithm to extract the centerline. Firstly, the best representation of vessel cross section on orthogonal planar is determined. Then, the center of gravity from the crosssection is computed as centerline point iteratively. Branching detection and termination are invoked in this proposed method. We demonstrate the results quantitatively and qualitatively. In addition, we benchmark OPS with three state-of-the-art methods and illustrate the comparison results in radar chart (also known as spider chart). Finally, we discuss limitations of OPS and future works.